Perioperative management of a girl with hemophilia B undergoing dorsolumbar spine posterior instrumentation - Martinho, Liliana; Perry da Câmara, Luisa; Batalha, Sara; Rodrigues, Joana; Carioca, Filipa; Marques, Joana (Journal of the Portuguese Society of Anesthesiology, 2022)
Hemophilia B is a coagulation disorder characterized by a deficiency of clotting factor IX. Women are often heterozygous carriers of the disease, however if their clotting factor levels are less than 60%, they may have an increased bleeding tendency. This is even higher if levels are under 40%. We present a case of a 14-year-old female, with mild hemophilia B (hemophilia B carrier with factor IX level < 40%) who underwent a major surgery: a posterior spinal instrumentation from D6 to L1. The perioperative management was discussed, including the perioperative administration of blood products and coagulation adjuncts. This was coordinated by a multidisciplinary team (orthopedists, anesthesiologists, hematologists and nurses) to provide the best perioperative care and follow-up. Close collaboration and communication among/with the team members and the patient/family was vital throughout.